Application of machine learning techniques on the context of livestock analysis - Islam, Md. Shajedul; Masud, Syed Tahmid; Tawheed, Bhuiyan Mustafa (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.